2017
DOI: 10.1002/chem.201703270
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Bridging Group in Bis‐Pyridyl Ligands: Enhancing Both the Photo‐ and Electroluminescent Features of Cationic (IPr)CuI Complexes

Abstract: We report on the benefits of changing the bridging group X of bis-pyridyl ligands, that is, Py-X-Py where X is NH, CH , C(CH ) , or PPh, on the photo- and electroluminescent properties of a new family of luminescent cationic H-heterocyclic carbene (NHC) copper(I) complexes. A joint experimental and theoretical study demonstrates that the bridging group affects the molecular conformation from a planar-like structure (X is NH and CH ) to a boat-like structure (X is C(CH ) and PPh), leading to i) four-fold enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…In short, Costa and co‐workers have explored the possibility to prepare heteroleptic blue‐emitting compounds with N ^ N ligands with high energy lowest unoccupied molecular orbital (LUMO) levels, achieving yellow‐emitting devices due to the lack of a thermally activated delayed fluorescence (TADF) process . However, the same authors proposed to use another family of Cu(I) complexes bearing different N ‐heterocyclic carbenes and dipyridylamine ligands–, i.e., di‐iso‐propylphenyl)imidazole‐2‐ylidene and 2,2ʹ‐bis‐(3‐methylpyridyl)amine, showing an effective TADF emission that led to the first blue‐emitting Cu(I)‐iTMC LECs . Other studies by Zhang et al, Bolink and co‐workers, and Costa and co‐workers showed green‐ and yellow‐emitting Cu(I)‐iTMC based devices by changing the pattern substitution of heteroleptic diamine and diphosphine ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In short, Costa and co‐workers have explored the possibility to prepare heteroleptic blue‐emitting compounds with N ^ N ligands with high energy lowest unoccupied molecular orbital (LUMO) levels, achieving yellow‐emitting devices due to the lack of a thermally activated delayed fluorescence (TADF) process . However, the same authors proposed to use another family of Cu(I) complexes bearing different N ‐heterocyclic carbenes and dipyridylamine ligands–, i.e., di‐iso‐propylphenyl)imidazole‐2‐ylidene and 2,2ʹ‐bis‐(3‐methylpyridyl)amine, showing an effective TADF emission that led to the first blue‐emitting Cu(I)‐iTMC LECs . Other studies by Zhang et al, Bolink and co‐workers, and Costa and co‐workers showed green‐ and yellow‐emitting Cu(I)‐iTMC based devices by changing the pattern substitution of heteroleptic diamine and diphosphine ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we could use ionic host–guest systems based on ionic FCPs, by which efficient white emission can be realized by using very small amounts of [Ir(ppy) 2 (biq)] + (PF 6 ) − . Additionally, the introduction of a T 1 energy upconversion mechanism, such as thermally activated delayed fluorescence (TADF), could be useful for future material development …”
Section: Resultsmentioning
confidence: 99%
“…[refcodes CASXUQ (Elie et al, 2017), HEWPIL (Gornitzka & Stalke, 1994), MPYHGA (Marti et al, 2005), SAXVOD (Zhang et al, 2005), YIFJEC (Canty et al, 1980)]. Of the previously mentioned organometallic complexes, only the Zn II chloride complexed with di-2-pyridylketone structure (LUCBOA; Katsoulakou et al, 2002) has a tetrahedral coor- interactions between adjacent molecules of the title complex.…”
Section: Structure Descriptionmentioning
confidence: 99%